Dyspnea and Wheezing after Adenosine Injection in a Patient with Eosinophilic Bronchitis - Rodrigo Cartin-Ceba; Marie Christine Aubry; Kaiser Lim (Case Reports in Medicine)
A 58-year-old nonsmoker female was referred for evaluation of chronic cough of 13 months duration. After an initial work-up, the patient was diagnosed to have chronic cough due to eosinophilic bronchitis. The diagnostic work-up for eosinophilic bronchitis and bronchial biopsy is discussed. Eosinophilic bronchitis is differentiated from asthma. In addition, the patient developed dyspnea, flushing, and wheezing after the administration of adenosine during a cardiac stress test in spite of a negative methacholine challenge. This indirect stimulus of airway hyperresponsiveness suggests the possible involvement of mast cells in eosinophilic bronchitis.